PERILAKU DEMOKRATIK MASYARAKAT VIRTUAL (STUDI KASUS PEMUSTAKA PERPUSTAKAAN UIN SUNAN KALIJAGA YOGYAKARTA) - Shinta Nofita Sari (Jurnal Pustaka Ilmiah, 2019)
This research was conducted at the State Islamic Library of Sunan Kalijaga (UINSUKA) Yogyakarta, the purpose of this study was to find out how the democraticbehavior of virtual communities. The research method used is descriptive researchwith a qualitative approach. The informants in this study were library representativesfrom all library users of UIN SUKA. The results of this study indicate that 1) thebehavior of users of internet use is reviewed from the uses and gratification theory,namely to meet cognitive, affective, personal and social needs not always fulfilledwith the use of internet networks, 2) library UIN SUKA knows the internet for the firsttime at the time of junior high school (SMP) as many as 4 people and 1 person knewthe internet for the first time during grade 6 elementary school (SD), 3) the interestsof the library library UIN SUKA using the internet at this time as a whole to meet theinformation needs of users, intensity of internet usage by UIN SUKA Library users,that is, the entire library mentions the use of the internet in accessing and searchingfor something> 3 hours / day, then in 1 month the user uses the internet> 90 hours,therefore the user exceeds 40 hours in 1 month then called as Heavy Users.Keywords: Democratic Behavior, Virtual Society